Antibacterial Activity of Green Synthesis of Iron Nanoparticles Using Lawsonia inermis and Gardenia jasminoides Leaves Extract. (21st January 2015) - Naseem, Tayyaba; Farrukh, Muhammad Akhyar
Abstract : Recently, development of reliable experimental protocols for synthesis of metal nanoparticles with desired morphologies and sizes has become a major focus of researchers. Green synthesis of metallic nanoparticles has accumulated an ultimate interest over the last decade due to their distinctive properties that make them applicable in various fields of science and technology. Metal nanoparticles that are synthesized by using plants have emerged as nontoxic and ecofriendly. In this study a very cheap and simple conventional heating method was used to obtain the iron nanoparticles (FeNPs) using the leaves extract of Lawsonia inermis and Gardenia jasminoides plant. The iron nanoparticles were characterized by thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray diffraction (XRD). The antibacterial activity was studied against Escherichia coli, Salmonella enterica, Proteus mirabilis, and Staphylococcus aureus by using well-diffusion method.